Transtibial prosthetic socket fitting: Australian prosthetist perspectives on primary challenges, management strategies, and opportunities for workflow and technological innovation. - Armitage, Lucy; McDonald, Kirsty A.; Kark, Lauren; Buller, Angela; Ford, Belinda (Prosthetics & Orthotics International, 2023)
Background: Following transtibial amputation, a custom-built socket is the most common interface between the prosthesis and residual limb. Desire from both prosthetists and prosthesis users for improved socket fitting processes have been well documented. However, there is currently limited information available about prosthetists' experiences of how prosthetic manufacturing workflow can contribute to socket fit problems. Objectives: This study aims to determine how socket fit problems are currently detected and managed by prosthetists and to identify challenges, management strategies, and opportunities for workflow and technological innovation during prosthesis manufacture and socket fitting. Study design: Mixed-method (quantitative and qualitative) survey. Methods: An online survey was developed and piloted in consultation with members of the Australian Orthotic Prosthetic Association. The final 25-question survey was distributed through their membership database. Mixed methods were used to analyze survey items. Qualitative items were grouped and coded under themes relating to challenges, management strategies, and opportunities. Quantitative data were analyzed using nonparametric descriptive methods. Results: Twenty-three respondents with a range of experience completed the survey. Seven of eight major Australian states/territories were represented. Primary workflow stages presenting challenges with limited strategies/solutions available to the prosthetists were roll-on liner selection, mold or cast modifications, communication with the client, and check socket fitting. Suggested solutions included improved socket–limb interface monitoring technology. Conclusions: This study provides the first insights into prosthetist-identified challenges and limitations at different stages of the socket workflow and presents a starting point for more targeted research into innovation that may assist in these processes.